Micropropagation as a Tool for the Conservation of Autochthonous Sorbus Species of Czechia - Šedivá, Jana; Velebil, Jiří; Zahradník, Daniel (Plants (Basel, Switzerland), 2023)
Members of the genus Sorbus are the only endemic tree species that occur in Czechia. They are important components of endangered plant communities. Their natural regeneration is usually problematic because of their mode of reproduction and because they can survive in rare populations with small numbers of individuals. The aim of this study was to develop a successful micropropagation protocol for selected Sorbus species, of which two are endemic (S. gemella and S. omissa) and two are hybrid (S. × abscondita and S. × kitaibeliana). We found significant differences in shoot induction and rooting ability between the Sorbus species under study. With the exception of S. × abscondita, N6-benzyladenine had a significantly greater effect on shoot regeneration, both in terms of shoot number and total shoot length, than meta-topolin. Root induction was key to the successful micropropagation of the Sorbus species studied. Our results show that four Sorbus species can be successfully rooted under ex vitro conditions, without a rooting powder treatment in a steamed peat-perlite substrate. Auxin-untreated microcuttings of S. gemella, S. × kitaibeliana and S. omissa, but not S. × abscondita, rooted better than ones treated with indole-3-butyric acid. This is the first time a micropropagation protocol for S. omissa, S. × abscondita and S. × kitaibeliana has been published.
Keywords: endemic species; micropropagation; ex vitro rooting; Sorbus; substrate